PowerVM, The Server Virtualization Without Limits - Nachappa, M N; Rani, Mary Merline; Mrinmoyee, Mrinmoyee (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper is about PowerVM virtualization technologies. Maintaining Web performanceduring peak periods requires dynamic scalability, but achieving that kind of scalability oftenmeans overspending on an infrastructure that is underutilized most of the time. Virtualmachine technology, or virtualization, is gaining momentum in the information technologycommunity since it can satisfy peak scalability requirements without a costly, oversizedinfrastructure by replacing or complementing the physical servers with virtual ones. Virtualserver services are designed to help reduce the cost and complexity of current Linux, AIX orOS/400 based infrastructure. It is the first multiplatform portfolio of virtual solutions for ebusiness.Recent advances in hardware and software technology have brought virtualizationto the forefront of IT management .PowerVM allows business units to consolidate multipleworkloads onto fewer systems, increasing server utilization, and reducing cost.